THE EFFECTIVENES OF USING AUDIO-VISUAL MATERIALS FOR EXTENDED DIALOGUES AND MONOLOGUES LISTENING TEXTS - Yuniar, Rendhi Fatrisna (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Listening is the initial language skills mastered by language learners as the investment to develop their other language skills. Hence, an appropriate listening lecture is necessary to assist language learners to develop the other language skills optimally. Nevertheless, the majority of teachers use audio materials to teach listening which does not represent the actual elements in the real communication situation. Therefore, this research was aimed to investigate the effectiveness of exerting audio-visual materials for extended dialogues and monologues listening texts since this kind of materials provides the students with realistic situations in communication. To achieve the purpose, a quasi-experimental research was administered by involving two out of three classes at SMKN 5 Malang majoring at software engineer as the respondents. They were determined by analyzing their previous listening scores by using Analysis of Variance (ANOVA). XI RPL 3 (as the experimental group) was taught listening by using audio-visual materials whereas XI RPL 2 (as the control group) was taught listening by using audio materials. The treatments were given in two meetings whereby at the end of the treatments, both groups were given a post-test to figure out whether or not the scores gained by the experimental group and the control group are significantly different. The result of the post test was analyzed by using independent sample t-test by using SPSS in which the output showed that there was a significant difference in students’ listening scores. Audio-visual materials were found effective to assist the students in the experimental group to achieve higher score compare with the students in the control group. As a result, audio-visual materials are strongly suggested to teach listening especially for extended dialogues and monologues listening texts.